1981
DOI: 10.1620/tjem.135.237
|View full text |Cite
|
Sign up to set email alerts
|

Changes in lymphocytes as an early sign of relapse in adult acute leukemia.

Abstract: This study was undertaken to find out some clue to detect early relapse of adult acute leukemia which had been in remission. Laboratory data such as LDH, erythrocyte sedimentation, or immunoglobulin level did not show any difference at the time of relapse from the remission period. Complete blood count with reticulocyte count was evaluated every two weeks retrospectively for 12 weeks before relapse. No significant change was observed at the time of relapse. However, both the percentage and absolute number of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1984
1984
1984
1984

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…According to our previous case study (Kawamura et al 1981), the relapse was confirmed by bone marrow puncture in 10 of 12 cases (83%) in which the peripheral lymphocyte value was raised over 45%. The leukemic cells in the bone marrow were 10% or less at the time of relapse in 4 of the 10 cases and those in the peripheral blood were 0% in 9 cases.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…According to our previous case study (Kawamura et al 1981), the relapse was confirmed by bone marrow puncture in 10 of 12 cases (83%) in which the peripheral lymphocyte value was raised over 45%. The leukemic cells in the bone marrow were 10% or less at the time of relapse in 4 of the 10 cases and those in the peripheral blood were 0% in 9 cases.…”
Section: Discussionmentioning
confidence: 84%
“…In the previous study (Kawamura et al 1981), i.e., the criterion was established to detect the relapse of adult leukemia in its early stage, when the share of lymphocytes in peripheral blood increased over 45% of the leucocytes during the maintenance therapy, bone marrow puncture was immediatly performed to examine the appearance of leukemic cells. By this criterion, the relapse was detect earlier than by other criteria.…”
mentioning
confidence: 99%